PENGARUH KOTORAN KAMBING TERHADAP PERTUMBUHAN VEGETATIF BIBIT KELAPA SAWIT (Elaeis guineensis jacq) DI PRE NURSERY DENGAN MENGGUNAKAN METODE HIDROPONIK - Aulia Juanda; Saroha Manurung; Ingrid Ovie Yosephine; Monang Antonius Purba (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2023)
MONANG ANTONIUS PURBA. 2020. THE EFFECT OF GOAT DIRTY ON THE VEGETATIVE GROWTH OF OIL PALM BIBT (Elaeis guineensis jacq) IN PRE NURSERY USING HYDROPONIC METHOD. Final Project of STIPAP Student of Plantation Cultivation Program. This research was supervised by Mr. Aulia Juannda Djs, S.Si., M.Si and Mrs. Ingrid Ovie. Y. Sitompul. This research was conducted in the STIPAP MEDAN greenhouse. When this research was conducted in April - July 2020. This study used the Hydroponic Method and used a completely randomized design as data processing. This research was conducted to determine the development of oil palm seedlings every 2 weeks. The vegetative growth of oil palm (Elaeis guineensis Jacq) in the pre-nursery using the hydroponic method using goat manure has no significant effect on most of the parameters observed except for plant height which has a significant effect. From the average observation of the effect of goat manure on the vegetative growth of oil palm seedlings (Elaeis guineensis Jacq) in the pre-nursery using the hydroponic method, it can be seen that the highest effect obtained is on the 2500ppm treatment, namely on plant height (19.85 cm), stem girth. (2.63 cm), and the number of leaves (3.31 cm). Meanwhile, the average yield of leaf chlorophyll and leaf width obtained the best results from the 1500ppm treatment, namely 24.99 cm stem girth and 3.39 cm leaf width. The conclusion that can be drawn from the results of this study is that the dose at the 2500ppm treatment is right for use in the hydroponic method and it is hoped that this research can be developed by looking for other organic fertilizers to be combined with goat manure with the best dose, so that the nutrient content that has been added is more complete. there is. And continued research was carried out at the Main Nursery (MN).